Cartographic grounds : projecting the landscape imaginary - Desimini, Jill; Waldheim, Charles (New York : Princeton Architectural Press, 2016)
"Mapping has been one of the most fertile areas of exploration for architecture and landscape in the past few decades. While celebrating this shift in representation from the material and physical description toward the depiction of the unseen and often immaterial, Cartographic Grounds takes a critical view toward the current use of data mapping and visualization and calls for a return to traditional cartographic techniques to reimagine the manifestation and manipulation of the ground itself. Each of the ten chapters focuses on a single cartographic technique--sounding/ spot elevation, isobath/contour, hachure/hatch, shaded relief, land classification, figure-ground, stratigraphic column, cross-section, line symbol, conventional sign-- and illustrates it through beautiful maps and plans from notable designers and cartographers throughout history, from Leonardo da Vinci to James Corner Field Operations. Mohsen Mostafavi, dean of the Harvard Graduate School of Design, introduces the book, a veritable atlas of contemporary maps and techniques that is as beautiful as it is useful"--
boek